A Multicenter Survey of Type I Diabetes Mellitus in Chinese Children - Hou, Ling; Li, Xiuzhen; Liu, Li; Wei, Hanyang; Xiong, Feng; Du, Hongwei; Yang, Yu; Zhang, Huifeng; Zhang, Qin; Yao, Hui; Fu, Junfen; Yan, Xiaoli; et al. (Frontiers in Endocrinology, 2021)
Purpose: To investigate the features and treatment status of type 1 diabetes mellitus (T1DM) children in China. Methods: The patients <14 years old from 33 medical centers in 25 major cities in China were enrolled from Jan. 2012 to Mar. 2015. All the patients finished the questionnaire conducted by their pediatric endocrinologists. Results: A total of 1,603 children (755 males and 848 females) with T1DM diabetes participated in the survey. Onset symptoms with diabetic ketoacidosis (DKA) and non-DKA were 834 (52.03%) and 769 (47.97%). Female has higher proportion (55.71%) from DKA onset cohort than that (49.33%) from non-DKA onset cohort. At the initial diagnosis, the proportions of anti-GAD， anti-IAA and anti-ICA positive accounted for 29.4%, 15.2% and 11.8%. The frequency of DKA under 3 years old was higher. Insulin pump was used in 244 patients (15.21%). Most of patients monitored blood glucose were less than 35 times per week. Even through majority of patients could receive drug in time, 4.74% of children could not receive medicine for financial reasons, shortage of insulin preparations and guardians’ failure to get the medicine. Diabetes education mainly relies on medical staff specifically engaged in the care of diabetes. Conclusion: Control of T1DM and health education in Chinese children remains a huge challenge for health workers and government.